2015
DOI: 10.1016/j.cell.2015.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gene Positioning Factors Using High-Throughput Imaging Mapping

Abstract: Summary Genomes are non-randomly arranged in the 3D space of the cell nucleus. Here we have developed HIPMap, a high-precision, high-throughput, automated fluorescent in situ hybridization imaging pipeline, for mapping of the spatial location of genome regions at large scale. High-throughput imaging position mapping (HIPMap) enabled an unbiased siRNA screen for factors involved in genome organization in human cells. We identify 50 cellular factors required for proper positioning of a set of functionally divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
176
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(197 citation statements)
references
References 56 publications
19
176
1
1
Order By: Relevance
“…Crosstalk can lead to errors in replication and repair, since repetitive heterochromatic regions pose a challenge to replication forks as they tend to stall at repetitive sequences and sometimes collapse; this can lead to loss of heterozygosity and, in severe cases, to the formation of chromosome bridges during mitosis (Mirkin, 2006). Interestingly, the observed involvement of replication and cell cycle regulators in both pairing and anti-pairing (Joyce et al, 2012) also suggests that faithful progression through the cell cycle is crucial for genome organization -a concept which also emerged from our recent gene-positioning screen in human cells (Shachar et al, 2015b).…”
Section: Box 1 Basic Organization Of Chromatin In the Nucleusmentioning
confidence: 76%
See 2 more Smart Citations
“…Crosstalk can lead to errors in replication and repair, since repetitive heterochromatic regions pose a challenge to replication forks as they tend to stall at repetitive sequences and sometimes collapse; this can lead to loss of heterozygosity and, in severe cases, to the formation of chromosome bridges during mitosis (Mirkin, 2006). Interestingly, the observed involvement of replication and cell cycle regulators in both pairing and anti-pairing (Joyce et al, 2012) also suggests that faithful progression through the cell cycle is crucial for genome organization -a concept which also emerged from our recent gene-positioning screen in human cells (Shachar et al, 2015b).…”
Section: Box 1 Basic Organization Of Chromatin In the Nucleusmentioning
confidence: 76%
“…The screen in human skin fibroblasts uncovered 50 cellular factors that are required for proper gene positioning, most of them not previously implicated in nuclear organization or gene positioning. Notably, most of the factors identified affected the positioning of some of the target loci but not all, indicating that gene positioning is not determined by a single dedicated machinery, but rather that multiple pathways and mechanisms contribute to position various loci and to organize compartments with diverse expression status and chromatin state (Shachar et al, 2015b). By monitoring expression levels of several genes following re-positioning it was shown that gene positioning is not tightly linked with activity, demonstrating that positioning and expression can be uncoupled, which is in line with previous findings (Therizols et al, 2014).…”
Section: Box 1 Basic Organization Of Chromatin In the Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…Great strides have been made in the realm of high-content DNA FISH microscopy approaches (hiFISH), which utilize automated image acquisition and analysis tools to interrogate DNA probe libraries. 21,29,30 Potentially, this approach can accurately quantify gene pairing events that occur across larger linear genomic distances and between chromosomes at high-resolution but current highcontent microscopy experiments are still limited to only 4 distinct fluorophores for visualization (one of which must be dedicated to a nuclear stain for automated image analysis). Therefore, current methods are inadequate for the co-visualization of multiple genes in conjunction with co-detection of chromosome territories, sub-nuclear structures and/ or distinct epigenetic marks.…”
Section: Introductionmentioning
confidence: 99%
“…Within TADs, gene regulatory clusters are kilobase-size nuclear domains created by functional interactions between promoters and enhancers Kieffer-Kwon et al 2013). This spatial architecture also varies from cell to cell (Nagano et al 2013) and changes in response to gene activation (Therizols et al 2014), spurring a wave of imaging studies seeking to better understand the nature of these compartments (Chen et al 2013;Williamson et al 2014;Beliveau et al 2015;Shachar et al 2015;Boettiger et al 2016). In one study, the "first passage time" (FPT) was determined for two regions of genomic DNA in the context of V(D)J recombination at the mouse IgH locus (Lucas et al 2014).…”
mentioning
confidence: 99%